COVID‐19 vaccinations: The unknowns, challenges, and hopes. Issue 4 (10th December 2021) - Mohamed, Kawthar; Rzymski, Piotr; Islam, Md Shahidul; Makuku, Rangarirai; Mushtaq, Ayesha; Khan, Amjad; Ivanovska, Mariya; Makka, Sara A.; Hashem, Fareeda; Marquez, Leander; Cseprekal, Orsolya; Filgueiras, Igor Salerno; et al.
Abstract: The entire world has been suffering from the coronavirus disease 2019 (COVID‐19) pandemic since March 11, 2020. More than a year later, the COVID‐19 vaccination brought hope to control this viral pandemic. Here, we review the unknowns of the COVID‐19 vaccination, such as its longevity, asymptomatic spread, long‐term side effects, and its efficacy on immunocompromised patients. In addition, we discuss challenges associated with the COVID‐19 vaccination, such as the global access and distribution of vaccine doses, adherence to hygiene guidelines after vaccination, the emergence of novel severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) variants, and vaccine resistance. Despite all these challenges and the fact that the end of the COVID‐19 pandemic is still unclear, vaccines have brought great hope for the world, with several reports indicating a significant decline in the risk of COVID19‐related infection and hospitalizations. Highlights: 1. Vaccination plays a pivotal role in reducing the death toll of the COVID‐19 infection. 2. The immunity provided by vaccines is still disputable leading to some challenges like the asymptomatic spread; therefore, staying strict to hygiene guidelines is necessary. 3. Hence, COVID‐19 vaccines' related long‐term side effects are still unknown; cautions should be taken when injected to various individuals of the community. 4. COVID‐19 vaccines' effectiveness are strongly related to their effect on emergent COVID‐19 variants, but until now approved vaccines can still show some protective effects against new variants.